Incendios forestales en el Estado de México en el periodo de diciembre de 1997 a junio de 1998 - Rivas Manzano, Irma Victoria; Fragoso Reyes, Nerea Josefina; García Medina, Jaime; Rivas González, Eric; Díaz Ascencio, Edith Patricia; Sánchez Colín, José Cruz (CIENCIA ergo-sum, 2017)
-